Treatment for stable HIV patients in England: can we increase efficiency and improve patient care?. (July 2014) - Adams, Elisabeth; Ogden, David; Ehrlich, Alice; Hay, Phillip
Objectives: To estimate the costs and potential efficiency gains of changing the frequency of clinic appointments and drug dispensing arrangements for stable HIV patients compared to the costs of hospital pharmacy dispensing and home delivery. Methods: We estimated the annual costs per patient (HIV clinic visits and either first-line treatment or a common second-line regimen, with some patients switching to a second-line regimen during the year). The cost of three-, four- and six-monthly clinic appointments and drug supply was estimated assuming hospital dispensing (incurring value-added tax) and home delivery. Three-monthly appointments and hospital drug dispensing (baseline) were compared to other strategies. Results: The baseline was the most costly option (£10, 587 if first-line treatment and no switch to second-line regimen). Moving to six-monthly appointments and home delivery yielded savings of £1883 per patient annually. Assuming patients start on different regimens and may switch to second-line therapies, six-monthly appointments and three-monthly home delivery of drugs is the least expensive option and could result in nearly £2000 savings per patient. This translates to annual cost reduction of about £8 million for the estimated 4000 eligible patients not currently on home delivery in London, England. Conclusions: Different appointment schedules and drug supply options should be considered for stable HIV patients based on efficiency gains. However, this should be assessed for individual patients to meet their needs, especially around adherence and patient support.